Equine Parvovirus-Hepatitis Population Dynamics in a Single Horse over 16 Years - Alexandra J. Scupham (Viruses, 2025)
Many viruses mutate rapidly to adapt to host defenses, and for some of these viruses, the result is long-term infection in individual hosts. The work described here examines the infection and long-term maintenance of a newly identified virus, equine parvovirus-hepatitis (EqPV-H), in an individual horse. This description is possible because of a hypervariable region in the capsid gene; sequence variants were tracked by high-throughput sequencing of serum samples taken over a 16-year period. The data support the hypothesis that EqPV-H infection resulted in a sequence variant bottleneck. The continuing infection evolved into a complex viral population showing a pattern of emergence, dominance, and recession with replacement. This is the first temporal description of the capsid gene evolution of EqPV-H in a single animal.